2017
DOI: 10.1021/acs.jpcc.7b05373
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Stimuli Response of Doped MAun Clusters (n = 4–8; M = Si, Ge) at Discrete Temperatures: A BOMD Undertaking

Abstract: Gold clusters are emblematic members of the family of nanofunctional materials with unique properties that can be customized through the incorporation of impurities. One such controllable property is catalytic activity. Experimental investigations have demonstrated that, upon the addition of group-14-based atomic impurities such as Si, Ge, and Sn atoms, Au clusters demonstrate augmented catalytic behavior. The present work explores the structural response of such experimentally derived and catalytically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…[39][40][41][42] Few studies have been undertaken on the gold clusters doped with group-14 atoms. 26,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Small Si-doped gold clusters, such as Au 4 Si À1/0 , Au 4 Si 2 À1/0 , Au 2 Si 2 À1/0 , and Au 3 Si 3 À1/0/+1 , have been investigated by Wang et al 26,43,44 The Au/H analogy has been found in the tetrahedral Au 4 Si À1/0 cluster. For Ge or Sn dopant, they also affect the structure of gold clusters by different ways relative to the Si dopant.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] Few studies have been undertaken on the gold clusters doped with group-14 atoms. 26,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Small Si-doped gold clusters, such as Au 4 Si À1/0 , Au 4 Si 2 À1/0 , Au 2 Si 2 À1/0 , and Au 3 Si 3 À1/0/+1 , have been investigated by Wang et al 26,43,44 The Au/H analogy has been found in the tetrahedral Au 4 Si À1/0 cluster. For Ge or Sn dopant, they also affect the structure of gold clusters by different ways relative to the Si dopant.…”
Section: Introductionmentioning
confidence: 99%